Institutional learning and change in the CGIAR: summary record of the workshop held at IFPRI, Washington, D.C., February 4-6, 2003 - Mackay, Ronald; Horton, Douglas E. (International Food Policy Research Institute, 2003)
This report summarizes papers presented and the discussions that took place at the workshop on Institutional Learning and Change in the CGIAR. It addresses evaluation of agricultural research on poverty in developing countries. Some of the implications emerging from this workshop include: (1) designing evaluation that focus on the target audience's questions (as opposed to those that interest the evaluator). (2)selecting methods that best answer these questions and that optimize the relevance of the inquiry to organizational members (3) employing procedures that maximising the involvement and learning of organizational members and stakeholders (4) being proactive about communicating, as opposed to assuming that recipients will read & understand reports (5) for senior managers: ensuring that internal evaluators have a clear and formal mandate to support organizational learning (6) using evaluations to develop leadership.